Randomized study of once-weekly interferon β-1a therapy in relapsing multiple sclerosis: three-year data from the OWIMS study - Freedman, M S; Francis, G S; Sanders, E ACM; Rice, G PA; O'Connor, P; Comi, G; Duquette, P; Metz, L; Murray, T J; Bouchard, J-P; Abramsky, O; Pelletier, J; et al. (Multiple sclerosis, 2005)
Background: Once weekly interferon β-1a for multiple sclerosis (OWIMS) demonstrated modest, but significant, magnetic resonance imaging (MRI) benefit of once-weekly (qw) interferon (IFN) β-1a at 48 weeks, but no significant effect on relapses. Objective: An OWIMS extension permitted assessment of longer-term efficacy/safety of qw IFN β-1a in relapsing-remitting multiple sclerosis (RRMS). Methods: Placebo patients were rerandomized to IFN β-1a, 22 or 44 mcg qw, for two additional 48-week intervals. Primary outcome was MRI lesion activity. Relapse rate and other MRI measures were secondary outcomes. Results: After three years, median (mean) T2 lesion count/patient/scan was 1.3 (2.6) for 44 mcg, 1.7 (3.3) for 22 mcg, 1.7 (3.4) for placebo/22 mcg, 2.0 (3.6) for placebo/44 mcg (all differences not significant). Annualized relapse rates were lowest for 44 mcg (0.77) versus other groups (0.83-0.86, not significant). Persistent neutralizing antibodies did not affect relapse rates, but MRI active lesions were increased in antibody-positive patients receiving 44 mcg compared to antibody negative patients. Conclusions: In RRMS, once weekly IFN β-1a, particularly 44 mcg, can induce a significant MRI, but not relapse, effect, compared with placebo. No significant dose effect was seen. In contrast to the significant effect observed with three-times-weekly dosing of subcutaneous IFN β-1a compared with placebo, this study confirms the lack of meaningful clinical benefit with once-weekly dosing.